Differential Influence of Acupuncture Somatosensory and Cognitive/Affective Components on Functional Brain Connectivity and Pain Reduction During Low Back Pain State - Lee, Jeungchan; Eun, Seulgi; Kim, Jieun; Lee, Jun-Hwan; Park, Kyungmo (Frontiers in Neuroscience, 2019)
The underlying mechanism of pain reduction by acupuncture is still unclear, because acupuncture treatment involves multidimensional factors. In this study, we investigated the differential influence of acupuncture components on brain functional connectivity and on pain reduction. We used a specific form of sham acupuncture (phantom acupuncture; PHNT), which only has a needling-credibility (a belief that they were treated with real acupuncture needles), while real acupuncture (REAL) has a somatosensory needling stimulation, as well as a needling-credibility. Forty-three patients with low back pain were randomized into the REAL group (n = 25) and the PHNT group (n = 18). They underwent two pain steady-state fMRI runs implemented by a low back extension (LBE) pain model (lifting the low back using air-cuff inflation) before and after REAL or PHNT stimulation. Subjective pain ratings, perceived throughout the LBE runs due to the posture, were reported (LBEpain). The regions of interest were (1) the main nodes of the default mode network—the medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), (2) the main nodes of the salience network—the anterior/posterior insular cortices (a/pINS), and (3) the low back-specific region of sensorimotor network, S1back. Significant reductions in LBEpain were observed in both groups (REAL = -1.02 ± 1.53, PHNT = -1.26 ± 2.20). In REAL group, decreased LBEpain was positively correlated with decreased functional connectivity between the mPFC and pINS (r = 0.58, p < 0.05). Reduced LBEpain in PHNT was negatively correlated with increased PCC–aINS connectivity (r = -0.48, p < 0.05) and tended towards positive correlation with decreased S1back–pINS connectivity (r = 0.44, p = 0.07). Our findings might suggest different brain mechanisms of observed pain reduction; REAL seems to involve detachment of the self from the sensory aspect of pain, while PHNT does to shift attention to self and disengages physical pain processing hubs. This exploratory study proposes a sham methodology to dissociate the influence of different acupuncture components in acupuncture research. Further studies need to be followed with more elaborated hypothesis, study design, and analysis considering various cognitive/affective factors for better understanding of brain mechanisms of pain reduction regarding the different acupuncture aspects.